Kuerin matkassa: paikkaperustainen taideteos ympäristökonfliktissa - Jokela, Timo (Research in Arts and Education, 2021)
This article discusses a socially-engaged environmental art titled Kuer’s Journey and a related video work. The art work was created in the summer of 2018in collaboration with the Art Äkäslompolo art event. According to local wishes, the event critically considered the plan for the Hannukainen iron ore minetargeted next to the Äkäslompolo village near the Pallas-Yllästunturi National Park. Kuer’s Journey was carried out using an art-based action research approach to create a dialogic space and situation that serves as a tool for decolonisation and cultural revitalisation, while increasing community resilienceand adaptation, in inevitable environmental and cultural change in the Arctic. At the core of the article is the concept of Arctic art, which is used to reflecton the encounter between Western contemporary art practices and northern ecocultures and ways of knowing.